Gender Differences in Perceiving Advertising Texts - Arakelyan, Rouzanna; Sahakyan, Margarita (Armenian Folia Anglistika, 2013)
The concept of gender is one of the underlying means of creating effective advertising texts. The gender belonging, which ensures the impact and perception of ads, is conditioned by its thematic, linguo-stylistic and grammar characteristics. Certain gender belonging in a text can be indicated both directly and indirectly based on the stereotypes in the given culture. The firmer and more established the image about the social, psychological and biological characteristics of a certain interlocuter is, the more meaningful and impressive the information becomes. An advertising text is called effective and leads to some action if it takes into consideration the rules of speech impact and perception, as well as their relation to gender.